PRC1 promotes cell proliferation and cell cycle progression by regulating p21/p27-pRB family molecules and FAK-paxillin pathway in non-small cell lung cancer - Liang, Zhigang; Li, Xinjian; Chen, Jian; Cai, Haina; Zhang, Liqun; Li, Chenwei; Tong, Jingjie; Hu, Wentao (Translational Cancer Research; Vol 8, No 5 (September 30, 2019): Translational Cancer Research, 2019)
Background: This study aimed to demonstrate the function and molecular mechanism of protein regulator of cytokinesis 1 (PRC1) in the carcinogenesis of non-small cell lung cancer (NSCLC). Methods: Bioinformatics analysis was performed. Cell culture and plasmid construction were conducted for cell transfection. mRNA and protein expression, cell proliferation, migration, and cell cycle were detected. Mice models were also constructed. The relationship between PRC1 and the prognosis of NSCLC patients was analyzed. Results: PRC1 expression was higher in tumor tissues than adjacent non-tumor tissues (P